2019
DOI: 10.3233/cbm-181947
|View full text |Cite|
|
Sign up to set email alerts
|

α2δ1 may be a potential marker for cancer stem cell in laryngeal squamous cell carcinoma

Abstract: Cancer stem cells (CSCs) have the ability to dictate tumor initiation, recurrence, and metastasis. Here, we examined the expression of a 2 1 in laryngeal cancer tissues and further determined the effect of 2 1 on the migratory ability and tumorigenicity of laryngeal cancer cells. Immunofluorescence staining revealed that 2 1 was positive in 13 (13/16, 81.25%) cases in laryngeal squamous cell carcinoma (LSCC) tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Other types of cancer also contain a subset of α2δ1+ cells (small-cell lung cancer, laryngeal squamous cell carcinoma and gastric cancer), showing not only the same stem cell-like properties [197], but also the same chemoresistant phenotype [198] and overexpression of ERK1/2 [199]. In all cases, inhibition of α2δ1 has been proposed as a new promising therapeutic target for CSCs, including HCC CSCs [197][198][199][200].…”
Section: Mechanisms Of Resistance To Therapy Of Cscsmentioning
confidence: 99%
“…Other types of cancer also contain a subset of α2δ1+ cells (small-cell lung cancer, laryngeal squamous cell carcinoma and gastric cancer), showing not only the same stem cell-like properties [197], but also the same chemoresistant phenotype [198] and overexpression of ERK1/2 [199]. In all cases, inhibition of α2δ1 has been proposed as a new promising therapeutic target for CSCs, including HCC CSCs [197][198][199][200].…”
Section: Mechanisms Of Resistance To Therapy Of Cscsmentioning
confidence: 99%
“…Other authors showed that there were other types of cancer that contain α2δ1+ cells such as small-cell lung cancer, laryngeal squamous cell carcinoma, and gastric cancer, with nearly the same stem cell-like properties [12], resistant to chemotherapy [13], and overexpression of ERK1/2 [14]. Also, they showed that inhibition of α2δ1 may serve as a new promising therapeutic target for these CSCs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, García et al [147] reported that when the expression of calcium channel α2δ1 subunit was inhibited, migration, adhesion as well as spreading of myoblasts were impaired, whereas the L-type calcium maintained unaffected, suggesting a newfound function of the α2/δ1 subunit in extracellular signaling. Later studies have confirmed that calcium channel α2/δ1 subunit is a potential marker for CSCs in laryngeal squamous cell carcinoma [148] and in non-small cell lung cancer [149] . Zhao et al [11] identified α2/δ1 subunit as a LCSCs marker and developed its monoclonal antibody named 1B50-1, which had positive therapeutic effects on HCC xenograft by eradicating LCSCs.…”
Section: α2δ1mentioning
confidence: 89%